The Bantu Presbyterian Church of South Africa : a history of the Free Church of Scotland mission - Duncan, Graham A. (Edinburgh : Edinburgh University Press, 2022)
Examines the Free Church of Scotland Mission in South AfricaDraws substantially on primary and secondary sources from South Africa and ScotlandDemonstrates the exceptional activity of Scottish missionaries in the field of the development of Christian missionsIndicates the crucial role played by indigenous Christians in the growth of the mission. Establishes the history of South African Christianity in the context of racial segregation and apartheid.
Background to this study -- The origins and early development of Scottish Presbyterian Mission in South Africa, 1824-65 -- Rev. Tiyo Soga (1829-71) : a paragon of early indigenous leadership -- The role of mission councils in the Scottish Mission in South Africa, 1864-1923 -- The Rev. Edward Tsewu's dispute with the Free Church of Scotland Mission -- The Mzimba Secession, 1898 : a South African 'disruption' -- Presbyterianism in South Africa, 1897-1923 : to unite or not to unite? -- Preparations for the formation of the Bantu Presbyterian Church of South Africa, 1897-1919 -- The formation of the Bantu Presbyterian Church of South Africa, 1920-3 -- Mission to church - church to mission : the first ten years, 1923-33 -- Reaching out : the Bantu Presbyterian Church in South Africa and the Presbyterian Church of South Africa and Ecumenism, 1923-39 -- The Bantu Presbyterian Church in South Africa and Ecumenism, 1940-99 -- The end of mission councils : the Church of Scotland South Africa Joint Council, 1971-81 -- A young church in mission or maintenance mode? The Bantu Presbyterian Church of South Africa, 1923-99 -- The Bantu/Reformed Presbyterian Church and socio-political issues -- Bantu/Reformed Presbyterian Church women in leadership in ministry -- Conclusion : indigenous Presbyterians and missionaries : transferring contending roles and responsibilities.
Includes bibliographical references and index.
Online resource; title from PDF title page (JSTOR, February 13, 2023)
eBooks on EBSCOhost
Keywords: Bantu Presbyterian Church of South Africa; Free Church of Scotland; Free Church of Scotland; Presbyterian Church -- Missions -- South Africa -- History; Presbyterian Church -- South Africa -- History; Presbyterian Church -- Scotland -- History; Scotland -- Church history; Église presbytérienne -- Afrique du Sud -- Histoire; Église presbytérienne -- Écosse -- Histoire; Écosse -- Histoire religieuse; HISTORY / Europe / Great Britain; Presbyterian Church; Presbyterian Church -- Missions; Scotland; South Africa; Church history; History